Integrasi Nilai-Nilai Islam Dalam Pembelajaran Matematika Melalui Pendekatan Pemecahan Masalah Bagi Calon Guru - Rahma Arifin, Arelia; Ramadhani, Revana; Kusno, Kusno (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The integration of Islamic values in mathematics education is an innovative approach that emphasizes harmony between cognitive and spiritual aspects in the educational process.. In the context of 21 st- century education, mathematics is no longer understood solely as an exact science that is logical and rational, but also as means of character building and moral values. Islamic value-based mathematics learning enables students to understand mathematical concepts while fostering religious attitudes such as honesty (sidq), patience (sabr), and responsibility (amanah), This study aims to examine strategies for integrating Islamic values into mathematics learning through a problem-solving approach, particularly in the context of teacher education. The research method used is a Systematic Literature Review of 25 scientific articles published between 2015 and 2025 that are relevant to the theme of integrating Islamic values and mathematical problem-solving skills. The results of the review show that the problem-solving approach is an effective medium for internalizing Islamic values because it encourages students to think critically, reflectively, and morally. Islamic values can be integrated through problem contexts, learning strategies, and learning outcome reflections. This research has implications for the develoment of Islamic mathematics curriculum and learning design oriented towwards the formation of religious character and professional competence of prospective teachers. The integration of Islamic values in mathematics education is an innovative approach that emphasizes harmony between cognitive and spiritual aspects in the educational process.. In the context of 21 st- century education, mathematics is no longer understood solely as an exact science that is logical and rational, but also as means of character building and moral values. Islamic value-based mathematics learning enables students to understand mathematical concepts while fostering religious attitudes such as honesty (sidq), patience (sabr), and responsibility (amanah), This study aims to examine strategies for integrating Islamic values into mathematics learning through a problem-solving approach, particularly in the context of teacher education. The research method used is a Systematic Literature Review of 25 scientific articles published between 2015 and 2025 that are relevant to the theme of integrating Islamic values and mathematical problem-solving skills. The results of the review show that the problem-solving approach is an effective medium for internalizing Islamic values because it encourages students to think critically, reflectively, and morally. Islamic values can be integrated through problem contexts, learning strategies, and learning outcome reflections. This research has implications for the develoment of Islamic mathematics curriculum and learning design oriented towwards the formation of religious character and professional competence of prospective teachers.